Penerapan Reward dan Punishment untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMP Negeri 2 Tenggarong Seberang - Sulis Setiawati; Zainuddin Untu; Auliaul Fitrah Samsuddin (Universitas Islam Jember, 2023)
This study aims to determine the increase in mathematics learning outcomes through the application of reward and punishment. Typeiofiresearch is classroom action research with students in VIII E class at SMPiNegeri 2 Tenggarong Seberang as research subjects. The research was conducted for 2icycles. Data collection techniques include observation, assignments, end-of-cycle tests, and documentation. The data analysis technique uses narrative statistics, namely the presentation of data in tabular form, the average increase, and the percentage increase in the average learning outcomes. the results of the study show that the application of reward and punishment can increase students' mathematics learning outcomes. The average score of students' mathematics learning outcomes in cycle I was 68.9 with fewer criteria and a completeness percentage of 24%. In cycle II the average student mathematics learning achievement was 82.6 with good criteria and the percentage of completeness was 88%. the results of observations of teacher activities in cycle I and cycle II were classified as very good. the resultsiofiobservationsionistudent activities in cycle I were classified as lacking and in cycle II student activity was classified as very good. The conclusion of this study is that the application of reward and punishment can improve the student’s mathematics learning outcomes.